Superior vena cava replacement combined with venovenous shunt for lung cancer and thymoma: a case series - Dai, Wei; Dong, Jifu; Zhang, Hongwei; Yang, Xiaojun; Li, Qiang (Journal of Thoracic Disease, 2018)
Background: Superior vena cava (SVC) replacement is infrequently performed and technically challenging in low-volume centers. Venovenous shunt (VVS) technique is used to reduce SVC pressure during SVC replacement and has not been well reported. This study aimed to add information on this subject and evaluate the surgical outcomes of patients who underwent SVC replacement combined with VVS in our center. Methods: A retrospective analysis of six patients who underwent SVC replacement combined with VVS from September 2011 to February 2017 was performed. Clinical characteristics, pathological features, operative characteristics, postoperative outcomes, and the survival of the six patients were reviewed. Results: There were four males and two females with a median age of 44 years (range, 35–69 years). There were three lung cancer patients and three thymoma patients at a stage from IIIA to IVA. Five patients underwent induction therapy. Complete resection was performed on five patients. One patient underwent internal VVS, and the other five patients underwent external VVS. Prosthesis grafts were employed in five cases and autologous pericardium in one case. Three patients underwent single-vein reconstruction, and the other three patients underwent double-vein reconstruction. The median SVC clamping time was 75 minutes. There were no postoperative deaths or major complications. All patients were alive at follow-up, and no thrombosis was found in any of the grafts. Conclusions: SVC replacement combined with VVS is technically feasible and safe. Although VVS technique is not a must, it may make SVC replacement safer in inexperienced centers. Surgery-based multidisciplinary treatment for selected patients with type T4 lung cancer and SVC involvement or thymoma and SVC involvement may achieve a favorable long-term outcome.